Novel power cable - SHI CELUE (2016)
The utility model discloses a novel power cable, shield layer, insulating layer, oversheath including center conductor, conductor, center conductor is located the conductor and shields the in situ, center conductor shields a layer fixed connection with the conductor, the insulating layer is located outside the conductor shields the layer, and the conductor of telling shields layer and insulating layer fixed connection, the oversheath is located outside the insulating layer, oversheath and insulating layer fixed connection, power cable designing is novel, rational in infrastructure, convenient and practical. 本实用新型公开种新型电力电缆，包括中心导体、导体遮蔽层、绝缘层、外护套，所述中心导体位于导体遮蔽层内，所述中心导体与导体遮蔽层固定连接，所述绝缘层位于导体遮蔽层外，所诉导体遮蔽层与绝缘层固定连接，所述外护套位于绝缘层外，所述外护套与绝缘层固定连接，所述电力电缆设计新颖，结构合理、方便实用。